Wives and work: Islamic law and ethics before modernity - Katz, Marion Holmes (Columbia University Press, 2022)
"It is widely known today among ordinary Muslims and scholars of Islam that classical Islamic law denies that wives have any obligation to do housework. Their exemption from domestic labor became a talking point among Muslims responding to Orientalist stereotypes of the "oppressed Muslim woman" by the late nineteenth century, and it was a prominent motif in writings by Muslim feminists in the US starting in the 1980s. More recently, Kecia Ali has pointed to the problematic doctrinal underpinnings of this rule in an early Islamic work in legal logic that posited wives to be "selling" their sexual availability (but not their labor) to their husbands. This study examines the historical analysis of this issue among Sunni legal scholars of the ninth to fourteenth centuries CE, showing that there was a much more complex discussion than previously known. As early as the ninth century, the prevalent legal doctrine that wives had no legal duty to do housework stood in conflict with what most scholars understood to be morally and religiously right and good. Their efforts to resolve this tension resulted in a range of solutions, from delineating a clear distinction between legal claims and ethical ideals to forging a complete synthesis of the two. Scholars' models of what was morally and religiously right drew on multiple discourses, from reports about the precedents set by the Prophet Muhammad to the Greek-derived discipline of philosophical ethics (akhlāq). As a result, the issue of wives' domestic labor offers a unique lens for considering questions about the relationship between Islamic law and ethics that have long been debated by scholars in the western academy"--